2017
DOI: 10.7127/rbai.v11n300555
|View full text |Cite
|
Sign up to set email alerts
|

Water Infiltration Rate in Distroferric Red Latosol Under Different Cropping Systems

Abstract: This study aimed to evaluate the water infiltration, hydraulic conductivity and hydraulic diffusivity in distroferric Red Latosol under different conditions of agricultural and livestock use. The different conditions of agricultural use and soil livestock are as follows: Cultivation of sugarcane, Annual crops, Crop-Livestock-Forest Integration Systems and Permanent Cerrado. Water infiltration in the soil was determined "in situ" by the method of cylinder infiltrometers and empirically through models Kostiakov,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…In this context, several studies have reported that agroforestry or integrated production systems, when compared to conventional systems, result in improvements in soil quality regarding the physical (Chen et al 2017;Moreira et al 2018;Cabral Filho et al 2017), chemical (Schwab et al 2015;Arau ´jo et al 2017;Pardon et al 2017) and biological properties (Udawatta et al 2014;Portilho et al 2018;Guillot et al 2019). These conservationist systems are also considered as a strategy for mitigating climate change, as they can promote atmospheric C sequestration (Lorenz and Lal 2014;Srinivasarao et al 2014;Abbas et al 2017;Tumwebaze and Byakagaba 2016;Dhillon and Rees 2017;Franzluebbers et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several studies have reported that agroforestry or integrated production systems, when compared to conventional systems, result in improvements in soil quality regarding the physical (Chen et al 2017;Moreira et al 2018;Cabral Filho et al 2017), chemical (Schwab et al 2015;Arau ´jo et al 2017;Pardon et al 2017) and biological properties (Udawatta et al 2014;Portilho et al 2018;Guillot et al 2019). These conservationist systems are also considered as a strategy for mitigating climate change, as they can promote atmospheric C sequestration (Lorenz and Lal 2014;Srinivasarao et al 2014;Abbas et al 2017;Tumwebaze and Byakagaba 2016;Dhillon and Rees 2017;Franzluebbers et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2016),Cabral Filho et al (2017) e Gomes Filho et al (2019, a medida da taxa de infiltração da água no solo é considerada um bom indicativo da verificação da sua qualidade física.…”
unclassified